NON-GOVERNMENTAL ORGANIZATION AS AN ENABLER TO SUPPLEMENT GAPS IN HEALTHCARE ACCESSIBILITY AND DELIVERY IN RURAL INDIA - Vasa, Prakash (Global journal of Business and Integral Security, 2022)
The purpose of this research study was to identify and validate gaps in rural healthcare infrastructure and provide a viable operational model for a Non-Governmental Organization to provide solutions to meet the timely needs of socioeconomically challenged rural populations. The study included analysis of 2011 census data from Government of India to understand the demographics and socio-economic conditions. The Data clearly identifiesincredibly low literacy levels with most of the population dependent on agriculture economy.Although a lot of progress has been made to alleviate the poverty problems in India, according to world bank data, about 176M of Indian population still remains below the poverty line. Three rural locations were identified for a use case for this study which included analysis of the census data of the local populationto understand the demographics. A patient transportation trial service was launched using custom manufactured Bike Ambulances in these three location and patient transport activities were documented using an Online Service Request system. The trial ran for a seven-month period from March through September 2021. Data collected was used to analyze, to make quick adjustments and find a sustainable NGO operational model. A number of operational adjustments were made to finetune the operations framework to ensure smoother service.A thorough survey of participants from every social class from these locations was conductedpost COVID-19 Second wave from July 2nd week to September 2nd Week, to further analyze the populations view on current healthcare infrastructure and gaps. Another Use Case was identified to support urban population suffering from Covid-19 Second wave and the lockdowns which stalled the economy. Multiple services were offered during this use case study and valuable data was collected. Although, the census data showedhigher literacy in the urban area but due to lockdowns and slowed downeconomy, people and patients needed a lot of helpwith necessities like medication, groceries, and hot meals. COVID-19 effected patients who were self-quarantined needed COVID-19 Medical kits. Transportation was limited with skyrocketing costs. The poor needed transportation services to the government hospitals with free medical care. Overall, the research has verified that gaps in the healthcare delivery in rural areas. Also, lower literacy rates have a profound effect on the rural populationshealthcare needs. NGO solutions with a self-sustaining operational model as an extension of the rural infrastructure both public and private is a viable option. The NGO provided services can be customized to the needs of the local populations.NGO solutions with a self-sustaining operational model as an extension of the rural infrastructure both public and private is a viable option to provide services as per the needs of the local populations. Since affordability has proven to be a big challenge, providing free or near free transportation services to the rural population is a win-win proposition. Delivering services which are need of the hour is essential to serve the community to the best possible extent.